PENGARUH DAYA TARIK IKLAN DAN PENDUKUNG SELEBRITI TERHADAP CITRA MEREK DAN NIAT BELI SHAMPOO PANTENE - Citra Saraswati; Suharno Suharno; Gusti Noorlitaria Achmad (Institut Bisnis dan Teknologi Pelita Indonesia, 2020)
The purpose of this research is to analyze and prove the effect of the attractiveness of advertisements and endorser celebrities on brand image and buying interest. The population used in this study were all consumers who used the